Experimental investigation of propagation of wetting front on curved surfaces exposed to an impinging water jet. (18th December 2008) - Akmal, M.; Omar, A.M.T.; Hamed, M.S.
The wetting phenomenon during the cooling of a hot cylindrical specimen exposed to an impinging water jet has been studied experimentally. The Speed of Propagation of Wetting Front (SPWF) and regions of boiling heat that transfer outwards from the jet stagnation point have been investigated using high-speed video images. The effect of various jet parameters (velocity, diameter, water temperature) and the effect of the surface temperature on SPWF have been considered. Experiments were conducted under transient conditions considering initial specimen surface temperatures of 250°C, 500°C and 800°C, water temperatures in the range between 20°C and 80°C, jet velocities of 5 m/s and 7.75 m/s and jet diameters of 3 mm and 4 mm. For all of the jet and surface parameters considered in the study, SPWF was found to correlate well with power functions of time (i.e., instantaneous wetting front radius R&#61a(t)n)). Within the considered range of parameters, the results indicate that SPWF is mostly affected by the initial surface temperature, water temperature and jet velocity. Since control of the product microstructure is the key in determining its mechanical properties, the results of the investigation of the SPWF are used to quench carbon steel (1045) cylinders using different combinations of jet parameters. The results show a great flexibility in achieving various cooling rates, as indicated by the change in the final microstructure of the quenched samples.